Analysis of reinforced concrete beam using STAAD-III release 22.3a / Shaharudin Shah Zaini - Shah Zaini, Shaharudin (Faculty of Civil Engineering, 1998)
The finite element method is a numerical procedure for analysing structures and continua and originated as a method of stress analysis. Today finite elements are also used to analyse problem not only in structural but its application has extended to include problems of heat transfer, geotechnic, fluid flow, lubrication, electric and magnetic flows and many others. In structural analysis, the application of forces to a structure produces stress and deformation. Stresses and deformation can be severe in magnitude, depending on the amount of loading applied, duration or number of repetition and may cause material failure. This report is to analyse a simply supported reinforced concrete beam of high strength concrete (Grade 60). The analysis, done using finite element approach with the aid of STAAD-III Release 22.3a software, produced for estimating stresses and deflections of the beam and where ever possible, comparison with the experimental work will also be conducted [Rasul, 1996]